Status Hukum Anak Angkat dan Pemeliharaannya Pasca Perceraian Orang Tua Angkat - Ramadhina, Karin Dwi; Dalimunthe, Siti Nurul Intan Sari (Universitas Semarang, 2023)
This study aims to determine the status and responsibility of maintaining adopted children after divorce between adoptive parents. Due to the discussion of the topic of the status and responsibility of the maintenance of adopted children, there has been no discussion that has a focus on the rights of adopted children. The divorce of the child's adoptive parents creates uncertainty for the child regarding the existing legal status, not infrequently the perception among the community about the position of the adopted child and the condition of the adopted child who is a child who is maintained and considered like a legitimate child results in the fulfillment of all maintenance for the adopted child in terms of maintenance to provide welfare and protection of the adopted child. The research method used is normative juridical with a statutory approach and a conceptual approach. The results of this study are adopted children whose adoptive parents divorce will not change the legal status of the adopted child towards both adoptive parents and Child Maintenance and Protection becomes an obligation of these parents to be responsible, maintain, and prioritize the rights of adopted children even though they are divorced in accordance with several existing laws and regulations and forms of division in fulfilling maintenance obligations Basically, it does not have special provisions because the most important thing is to prioritize the welfare of the child through the maintenance of the child until the child has grown up. Penelitian ini bertujuan untuk mengetahui status dan tanggung jawab pemeliharaan anak angkat setelah perceraian antara orang tua angkatnya. Dikarenakan pembahasan topik mengenai status dan tanggung jawab pemeliharaan anak angkat belum ada pembahasan yang memiliki fokus pada hak-hak anak angkat. Perceraian orang tua angkat anak menimbulkan ketidakjelasan bagi anak tersebut mengenai status hukum yang telah ada, tidak jarang persepsi diantara masyarakat mengenai kedudukan anak angkat tersebut serta keadaan anak angkat yang merupakan anak yang dipelihara dan dianggap layaknya anak sah mengakibatkan harus terpenuhinya segala pemeliharaan terhadap anak angkat keadaan dalam hal pemeliharaan untuk memberikan kesejahteraan dan perlindungan anak angkat. Metode Penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil Penelitian ini yaitu Anak angkat yang orang tua angkatnya bercerai tidak akan merubah status hukum anak angkat tersebut terhadap kedua orang tua angkatnya dan Pemeliharaan dan Perlindungan anak menjadi sebuah kewajiban orang tua tersebut untuk bertanggung jawab, memelihara, dan mengedepankan hak-hak anak angkat walaupun sudah dalam status bercerai sesuai dengan yang tercantum pada beberapa Peraturan Perundang-Undangan yang ada dan Bentuk pembagian dalam pemenuhan kewajiban Pemeliharaan pada dasarnya tidak memiliki ketentuan khusus karena hal terpenting adanya tetap mengedepankan kesejahteraan anak melalui pemeliharaan anak tersebut sampai anak tersebut telah dewasa.